Secrets - Michaels, Fern (Michaels, Fern. Lost and found, 2022)
When an old steamer chest from an anonymous source arrives at Cullen and Luna Bodman's restoration shop and café, it is fascinating in its own right. But inside, Cullen discovers a locked diary accompanied by a letter, asking for the diary to be restored to its rightful owner. Luna sees this as a puzzle to be solved, but everyone isn't thrilled by her quest. Her budding relationship with U.S. Marshal Christopher Gaines comes under strain as he tries to talk her out of a wild goose chase. When the Bodmans unveil a surprising modern-day connection, it leads the brother and sister to wonder if the diary's secrets still hold power today -- Adapted from jacket.